The raped woman as a horrific sublime and the Bangladesh war of 1971. (December 2015) - Mookherjee, Nayanika
This article examines the relationship between aesthetics and politics when invoking the imagery of war-time rape. It explores the prevalent way in which the raped woman of the Bangladesh war of 1971 is imagined in contemporary Bangladesh through the circulation of rumours, narratives of encounters and photographs. In 1971, faced with a large number of rape survivors after the war, the Bangladeshi government publicly designated any woman raped in the war a birangona (meaning brave woman / war-heroine). Over the last 40 years in Bangladesh, there has existed a public memory of wartime rape through various literary, visual and testimonial forms. These aesthetic representations of the war-heroine can be understood through Rancière's politics by other means – of that of the distribution of the sensible – through the horrific sublime figuration of the birangona . As an idea that is not readily apparent, these diverse oral, visceral and visual strategies make the birangona visible and comprehendible as bhoyonkor (horrific). The figuration of the birangona as a horrific sublime also brings to the surface Lyotard's formulation of the 'encoding' – the underlying moral values and judgment – that are implicit in the feelings that enable the readability of the war-heroine. I interrogate these hegemonic affective aesthetics (the way wartime rape is often narrowly described) through a nuanced ethnographic account of the birangona's life trajectory. This less categorised, non-semiotic figuration of the birangona is the interventionary mode, the politics – in Rancière's formulation – through which this idea of the horrific sublime can be disrupted.